The Big Secret - Murray, William 1912-1995; Illustration by Hines, Marida (London Ladybird Books Ltd)
A reading scheme that uses the 'look and say' approach to learning to read. It introduces essential key words and regularly repeats it to assist with pronunciation and meaning
Include Color Illustration
Keywords: Readers -- 1950- -- Readers